Status Ekonomi dan Konservasi Ikan Air Tawar di Sungai Meureubo, Kabupaten Aceh Barat - Irhami S; Agusriati Muliyana; Fitria Rahmayanti (Jurnal Serambi Engineering, 2023)
The Meureubo river has the potential to provide a livelihood for West Aceh district Community in the field of fisheries with various local species. This research aims to examine the economic status and conservation status of freshwater fish found in the Meureubo river. The sampling locations were determined using purposive Random Sampling which can represent the estuary, mid and upstream areas of the river as well as several tributaries. The research location points were divided inti nine stations based on differences in environmental tone. The research results show that in terms of economic status, Tor tambra is a fish that is listed as having economic value because this fish is in great demand and has a high selling price. Meanwhile, from a conservation perspective, 33 species of freshwater fish were recorded in the Meureubo river, whose status was then identified via the IUCN websit (www.IUCN.org), with 2 of them being Near threatend (NT), 5 species being data Deficient (DD), 6 species have Not Evaluated (NE) satus, and 20 species have least concern (LC) status.